Reluctant 'Jailors' speak out: parents of adults with Down syndrome living in the parental home on how they negotiate the tension between empowering and protecting their intellectually disabled sons and daughters. (10th September 2012) - Foley, Simon
Abstract : Accessible summary: This study looks at the issue of the social lives of adults with Down syndrome who are living at home with their parents. Sometimes, for the very best of reasons, the parents of adults with Down syndrome try to prevent their adult son or daughter with Down syndrome from going out on their own, from having a boyfriend or a girlfriend etc. In this study, I talk to a group of parents about how they feel when they think about the kind of social life their sons and daughters with Down syndrome have. For example, I ask them are they happy with the amount of friends that their son or daughter has, whether their son or daughter has a boyfriend or girlfriend, whether they would like to see their son or daughter get married etc. Because of the role played by parents in the social lives of their intellectually disabled adult son or daughter, it is very important for everybody concerned with the quality of life enjoyed by adults with an intellectual disability to understand why their parents think and act the way they do. Summary: While the language of empowerment and human rights have taken centre stage in both the disability literature and disability service provision for adults with intellectual disabilities. One area where there exists a disconnect between theory and practice, in the Republic of Ireland at any rate, lies in the parental home and the role played by parents of adults with intellectual disabilities (this study focuses specifically on adults with Down syndrome) in acting as gatekeepers of their son or daughters social life. For the best of paternalistic reasons, many parents of adults with Down syndrome severely restrict the life choices of their adult sons or daughters. This is particularly the case when it comes to the regulation of their son or daughters sexuality, a possible effect of which may be to effectively deprive their intellectually disabled son or daughter of the opportunity of ever entering into an intimate sexual relationship with another human being. So are parents of adults with Down syndrome actually playing the role of 'reluctant jailors'? If yes, how do they navigate the enormously tricky terrain that characterises the Scylla and Charybdis like tension between trying to empower their adult son or daughter with Down syndrome while at the same time doing all they can to insure they come to no harm? This study interviews ten parents on the earlier issues, to gain a greater phenomenological understanding on the predicament that many parents of adults with Down syndrome believe themselves to be in.